2002
DOI: 10.1002/ijc.10601
|View full text |Cite
|
Sign up to set email alerts
|

Lack of β‐tubulin gene mutations in early stage lung cancer

Abstract: Objective Fibroblasts from patients with systemic sclerosis (SSc) have an activated phenotype characterized by increased synthesis of extracellular matrix (ECM) components. SPARC (secreted protein, acidic and rich in cysteine) regulates the deposition or assembly of ECM components. The aim of this study was to investigate the role of SPARC in SSc susceptibility by functional and genetic association studies. Methods Complementary DNA (cDNA) microarrays were used to obtain gene expression data on cultured dermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
2
3
1
Order By: Relevance
“…In 1999, -tubulin mutations were observed in serum DNA from one-third of non-small-cell lung cancer patients, those exhibiting the worst outcome [31]. However, this first report was not confirmed in later studies, either in lung [32][33][34] or other tumors [34][35][36][37]. Where was the problem?…”
Section: Point Mutations Of Tubulin and Drug Resistancecontrasting
confidence: 44%
“…In 1999, -tubulin mutations were observed in serum DNA from one-third of non-small-cell lung cancer patients, those exhibiting the worst outcome [31]. However, this first report was not confirmed in later studies, either in lung [32][33][34] or other tumors [34][35][36][37]. Where was the problem?…”
Section: Point Mutations Of Tubulin and Drug Resistancecontrasting
confidence: 44%
“…Moreover, this report suggested a relationship between the location of the mutations on b-tubulin and response to Taxol-based chemotherapy, since patients with and without mutations had dramatic differences in median survival, a finding, which if validated, would have profound implications in determining treatment options for patients with NCSLC. Several groups sought to confirm this initial study; however, the results have not been corroborated in these prospective studies (Kelley et al, 2001;Kohonen-Corish et al, 2002;Sale et al, 2002;Tsurutani et al, 2002), although silent polymorphisms have been reported. A recent study analysing 62 human breast cancer tumors also concluded a lack of b-tubulin mutations in these tumors, and documented the presence of a silent polymorphism at codon 217 (Hasegawa et al, 2002).…”
Section: Tubulin Mutations In Human Tumorsmentioning
confidence: 43%
“…Single nucleotide polymorphisms in the 3V untranslated region have also been described previously (refs. 22, 23;dbSNP:1054419 The vast majority of previous mutation analyses have employed J00314 as a reference, which differs from the recently published wild-type sequence (cDNA AF070600, genomic DNA AP00512) by eight nucleotides (22,36). Such findings are particularly important in a mutational analysis of h-tubulin, as mismatches between these reference genes have been reported as somatic mutations (21).…”
Section: Discussionsupporting
confidence: 43%